Economic Analysis of Innovation Development Processes in Agriculture of the Republic of Uzbekistan - I. B. Rustamova; M. M. Babadjanova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides econometric analysis of agricultural production efficiency in the Republic of Uzbekistan. As methodology for identifying the impact of land, labour resources and capital on the net output of agriculture Kobba - Douglas production function was used. The results of analyzing parameters of the production function let the authors make a conclusion about the necessity to work out a new concept of innovation development and a new model of efficient running of agriculture and its development on the basis of innovative technologies and agrarian sector diversification. The plotted econometric model is statistically reliable and it can show the state of the net output of Uzbekistan agriculture. Kobba – Douglas production function by the net output of Uzbekistan agriculture and factors affecting it, as well as all its parameters checked by Fisher criterion, Student t-criterion and Darbin – Watson DW-criterion showed that the function by parameters meet all the requirements, which testifies to the possibility to use the model (multiplying model in the form of variables’ product) for the current analysis and future forecast of the net output of the Republic agriculture. On the basis of system econometric analysis the forecast parameters of the net output up to 2025 were identified that were found by raising efficiency of innovative processes in agriculture.